Assessment of black and gold howler monkey (Alouatta caraya, Humboldt, 1812) populations in two new study sites in northeastern Argentina - Bay Jouliá, Rodrigo (2023)
Alouatta caraya has the southernmost distribution of the howler monkeys. While information about most populations remains limited, the forests this species inhabits are being altered continuously. We present data about populations of A. caraya from two new study sites in northeastern Argentina: the “Laguna Oca” Biosphere Reserve (RLO) (26°14´S, 58°10´W), and the “Las Lomas” Private Reserve (RLL) (27°23´S, 58°22´W). We conducted censuses along roads within forest patches in both areas to find groups of A. caraya, counting all visible individuals, and classifying them by sex and age. We found only mixed sex groups in both areas, with a density of 1.12 individuals/ha in RLO and 2.05 individuals/ ha in RLL. At other study sites in Argentina, A. caraya population densities vary from 0.11 to 3.25 individuals/ha, where forest continuity may be important in determining densities. Maintaining long-term study sites of A. caraya across different habitats will allow comparative analyses to explore the underlying mechanisms of behavioral, ecological, and demographic variability.